The use of PV to replace typical skylight and its energy generation for cooling and lighting in Malaysian atria / Ahmad Ridzwan Othman - Othman, Ahmad Ridzwan (Institute of Graduate Studies, UiTM, 2013)
Atrium is an architectural feature often found in commercial buildings in Malaysia and the top-lit type is the most common. Besides its architectural value as a spatial connector, the introduction of translucent material as its roof envelope could turn it into a large daylight catcher. Its ability to serve as a media to allow entry of sun into the building means that it could bring in both daylight as well as excessive solar heat. For buildings in the tropical climate zone such as Malaysia, maximizing solar gain is most undesirable, as this will increase the indoor temperature and consequently unnecessary amount of energy is needed to cool back down the internal spaces to an acceptable thermal comfort level. A good energy efficient strategy is to channel the intense solar heat away from the interior, and capture its energy resource. Photovoltaic (PV) panel or commonly known as solar panel converts solar energy into electrical energy. Its productivity depends largely on its solar exposure hours, the placement of its panels in terms of the slope angle and orientation to the sun. When applied in buildings, PV is referred to as Building Integrated Photovoltaic (BIPV). BIPV system is a relatively expensive investment, thus its application has to be carefully considered to achieve optimization. Theoretically replacement of the conventional glass skylight with PV panels, improves the energy efficiency of the atrium through electrical energy production of the PV panels. It offsets the additional energy required to cool down the space due to solar heat gain. This thesis was set up to achieve three main objectives – firstly was to determine the amount of energy production through a modeling of basic BIPV (Building Integrated Photovoltaic) configurations for installation in atria…